The Effect of Dividend Policy, Good Corporate Governance Mechanism, And Audit Quality on Agency Cost - Indra Kencana Mukti; Agus Maulana (Pusat Penelitian dan Pengabdian Pada Masyarakat (P3M) STIE Pasundan, 2023)
This study is to analyze the effect of dividend policy, good corporate governance mechanisms, and audit quality on agency costs in manufacturing companies that conduct IPOs on the Indonesia Stock Exchange in the 2017-2020 period. In Indonesia, there are many companies that have relationships with agency costs, especially companies whose managers and owners of capital are different, such as companies listed on the Indonesia Stock Exchange (IDX). This research is essentially a form of quantitative research that uses secondary data, namely the company's annual report. This study used a sample of 132 companies in the manufacturing sector. The technique for analyzing the data in this study test a regression model selection test, classical assumption test, multiple linear regression, f test, and individual hypothesis testing (t test). According to the results of data analysis, it can be concluded that dividend policy, audit committee, audit quality, and institutional ownership has no effect on agency costs. In the other hand, independent commissioners have a significant negative effect on agency costs.